Causality Analysis Between Economic News and Health Expenditures: The Case of Türkiye (Third Sector Social Economic Review, 2026)
This study analyzes the relationship between economic news and health expenditures within the context of examining the interaction between media and economic indicators. The research is based on monthly data covering the period 2022–2024. The data were obtained from official statistics published by the Turkish Statistical Institute (TUIK) and from TRT Haber. In this way, the analysis relies on both reliable national sources and secondary data frequently used in academic studies. The Granger Causality Test was employed as the main econometric method. The stationarity properties of the series were examined using the Augmented Dickey–Fuller (ADF) unit root test and the Phillips–Perron (PP) unit root test, after which the appropriate lag length was determined. The empirical findings indicate that there is no statistically significant short-run causal relationship between the number of economic news items and health expenditures. In other words, increases or decreases in economic news coverage do not have a guiding effect on health expenditures, and fluctuations in health expenditures do not directly reflect on the media agenda. The findings suggest that strengthening transparency in the management of health expenditures and providing regular and accessible information to the public constitute a critical requirement. In this context, it is recommended that public institutions increase data sharing and that the media place greater emphasis on qualified and analytical reporting.
Keywords: Health Economics and Finance; Health Expenditures; Media Economics; Economic Journalism; Granger Causality